Menimbang Kontorversi Pemaknaan Konsep Ahl Al-Kitāb dalam Al-Qur’an - Zulyadain Zulyadain (Ulumuna, 2012)
One of the controversy-laden terms in the discourse of Islamic theology is ahl al-Kitab. Different ways of interpreting the term through textual and contextual exegesis of the Qur’an verses concerning it have colored the history of Muslim beliefs about other religion and religious communities. This paper aims to probe the controversies and arguments through revealing paradigms that underlies any views that differ from each other. Compromising the controversy was considered very important. Therefore, in the context the difference of textual and contextual interpretation of the term, the author conclude that both interpretations should be understood as mutual inclusion rather than two separate points in terms of mutual exclusion. Textual interpretation discovers basic, objective meaning of the term in Qur'an, while the contextual interpretation discovers its contextual meaning, both linguistic and socio-cultural.